1991
DOI: 10.1139/f91-142
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Year-Class Strength of Different Perch (Perca fluviatilis) Populations in the Baltic Sea with Special Reference to Temperature and Pollution

Abstract: Variations in the year-class strength of perch (Perca fluviatilis) were analyzed among 23 populations in Baltic coastal areas distributed between 57 and 66°N using the age distribution in catches. In spite of large differences in abiotic and biotic factors, the variations in year-class strength were similar in 14 of these areas. The similarities could be attributed to large-scale weather variations influencing water temperature. Year-class strength was shown to be correlated with an index based on temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 1 publication
3
33
0
1
Order By: Relevance
“…The harvest of perch has increased in Lake Peipsi and strong year-classes of this species have occurred more frequently in Lake Säkylän Pyhäjärvi and in Lake Søbygaard, although in the latter it may also be attributed to a major reduction in nutrient loading. Other studies have also found strong year classes of perch to be associated with warm summers (Böhling et al, 1991;Lappalainen et al, 1996;Sarvala & Helminen, 1996;Mehner et al, 1998;Paxton et al, 2004), and in Lake Pyhäselkä in north -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 eastern Finland perch density increased with increasing temperature from 1975 to 2005…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The harvest of perch has increased in Lake Peipsi and strong year-classes of this species have occurred more frequently in Lake Säkylän Pyhäjärvi and in Lake Søbygaard, although in the latter it may also be attributed to a major reduction in nutrient loading. Other studies have also found strong year classes of perch to be associated with warm summers (Böhling et al, 1991;Lappalainen et al, 1996;Sarvala & Helminen, 1996;Mehner et al, 1998;Paxton et al, 2004), and in Lake Pyhäselkä in north -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 eastern Finland perch density increased with increasing temperature from 1975 to 2005…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, triggered by the more frequent warmer summers, strong year classes of perch 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 (Böhling et al, 1991;Sarvala & Helminen, 1996) have appeared more often in the 1990s and 2000s than in the 1970s or 1980s (Sarvala & Helminen, 1996 and unpublished), increasing predation on vendace, and we may expect this trend to continue.…”
Section: Lake Säkylän Pyhäjärvi: Major Decline In Vendacementioning
confidence: 99%
“…The year-class strength of pikeperch varies strongly between years , but the annual year-class variations of different populations show similar patterns over spatial distances of 300-500 km in Finland (Lappalainen and Lehtonen 2002). Such patterns are clear indications for the positive effects of climatic factors on year-class formations (Böhling et al 1991;Myers et al 1997;. The contribution of a strong year-class to the future fisheries may be significant, thus the understanding of the effects of temperature on the year-class formation is important.…”
Section: Introductionmentioning
confidence: 97%
“…Water temperature is known to have positive effects on the establishment of strong pikeperch year-classes (Böhling et al 1991;Kjellman et al 2003). As a new approach, we have calculated the year-class catch by summing the commercial catch in numbers from each year-class in successive years (indicating year-class strength), based on the reported catches and catch samples from the commercial fishery .…”
Section: Introductionmentioning
confidence: 99%
“…were particularly abundant in 1988 which was a very favorable year for spring spawning fish species e .g . perch (Bohling et al ., 1991) .…”
Section: Discussionmentioning
confidence: 99%